Gender policy analysis in South Asia - Buchy, Marlene; Bhattacharjee, Suchiradipta; Dikshit, Manya; Karki, Darshan; Pradhan, Melissa; Taneja, Garima (International Water Management Institute, 2024)
This methodology brief, developed within the CGIAR initiative on National Policies and Strategies, tackles essential questions about how gender is woven (or not) into the fabric of a policy document – and how to interpret and understand the results. This tool, centered around a list of questions to use systematically whilst interrogating policy documents, is primarily designed for policy researchers, but the questions can also act as a guide during policy design for policy makers.